Integrating chemistry education with modern ICT - Jiemuratova Aynura Amangeldievna (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
The integration of information and communication technologies (ICT) in modern education has made great changes in the pedagogical practice of various subjects, including chemical education. This paper explores the transformative potential of ICT in improving the teaching and learning of chemistry, emphasizing innovative methodologies and digital tools that enrich the learning experience. Through the use of ICT, teachers can create interactive learning environments that facilitate personalized learning, collaborative problem solving, and real-time data analysis. This article reviews case studies and empirical research to demonstrate the benefits of integrating ICT into chemistry education, highlighting its impact on student engagement, conceptual understanding, and practical application of chemical principles. In addition, it discusses challenges and considerations in implementing ICT-based strategies.